Bilateral central serous chorio-retinopathy in pregnancy presenting with severe visual loss - Chakraborti, Chandana; Samanta, Swapan Kumar; Faiduddin, Khandakar; Choudhury, Krittika Pal; Kumar, Sheuli; Mondal, Ramkrishna (Nepalese Journal of Ophthalmology, 2014)
Introduction: Bilateral central serous chorio-retinopathy is an unusual presentation.  Objective: To report a case of pregnancy-induced bilateral central serous chorio-retinopathy. Case: A thirty-year-old woman complaining of reduced vision in both the eyes was referred for ophthalmoscopic evaluation in her third trimester of pregnancy. The best-corrected visual acuity was 6/60 in the right eye and finger counting at four meters in the left. The funduscopic examination revealed serous macular detachment with white sub-retinal exudates in both the eyes. Optical coherence tomography sections through the macula demonstrated serous elevation of the retina and retinal pigment epithelial detachment in both the eyes. The serous macular detachment resolved and the patient recovered to the visual acuity of 6/6 in both the eyes after twelve weeks of delivery. The OCT showed resolution of the sub-retinal fluid and disappearance of the sub-macular exudate in the right eye, but the resolution was partial in the left eye.Conclusion: Pregnancy is a risk factor for CSCR and it can present with severe bilateral visual diminution.DOI: http://dx.doi.org/10.3126/nepjoph.v6i2.11711Nepal J Ophthalmol 2014; 6(12): 220-223